ผลของแอลกอฮอล์ต่อสมบัติของของผสมจุดเดือดคงที่ของเอทานอลกับน้ำ - เจษฎา บุญนำพา (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Determination procedure of ternary azeotropes has been proposed based on conventional liquid activity coefficient models, i.e. NRTL, UNIQUAC, and UNIFAC, together with vapour-liquid and vapour-liquid-liquid equilibria. Influence of another alcohol on ethanol-water azeotrope has been investigated. Ethanol separation process has been modeled with 3 distillation columns according to extractive distillation with ethylene glycol. Afterwards, the process has been modified as 2 columns with side-streams. Both process models have been employed for investigating effects of various alcohols on ethanol purity produced. Finally, the minimum energy requirement of the process has been estimated. Ternary azeotropes can be predicted with UNIFAC-VLE, NRTL-VLE and NRTL-VLLE. UNIFAC-VLE can predict more precisely than the others. With 3-column and 2-column processes, high purity ethanol, above 99.4%, can be produced by adding methanol instead of ethylene glycol. The processes require methanol to ethanol ratio of at least 1.56. Ethanol can be recovered more than 98%. However, methanol has losed by 0.03% and 0.06% for 3-column, and 2-column processes, respectively. The minimum total energy requirement has become 63.5 and 44.4 MJ/kg ethanol for 3-column and 2-column processes, respectively. In addition, ethylene imine and propylene imine can also be used for both processes. Although the processes have required less imines energy than methanol for similar separation, they have been losed greater than methanol.